2021
DOI: 10.1038/s41467-021-25081-w
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of dietary inositol into propionate and acetate by commensal Anaerostipes associates with host health

Abstract: We describe the anaerobic conversion of inositol stereoisomers to propionate and acetate by the abundant intestinal genus Anaerostipes. A inositol pathway was elucidated by nuclear magnetic resonance using [13C]-inositols, mass spectrometry and proteogenomic analyses in A. rhamnosivorans, identifying 3-oxoacid CoA transferase as a key enzyme involved in both 3-oxopropionyl-CoA and propionate formation. This pathway also allowed conversion of phytate-derived inositol into propionate as shown with [13C]-phytate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 81 publications
4
66
1
Order By: Relevance
“…None of these species was significantly modified in the present study. However, in agreement with previous studies, increments in the intestinal abundance of Anaerostipes were correlated to higher concentrations of plasma butyric acid (Shetty et al, 2020;Bui et al, 2021), which also showed a trend toward significantly higher values in the ileum of the CARN lambs. Moreover, an increase in Ruminoclostridium, a cellulosomeproducing bacterium being able to metabolize branched plant polysaccharides, such as xyloglucan, was also observed in the CARN group (Ravachol et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…None of these species was significantly modified in the present study. However, in agreement with previous studies, increments in the intestinal abundance of Anaerostipes were correlated to higher concentrations of plasma butyric acid (Shetty et al, 2020;Bui et al, 2021), which also showed a trend toward significantly higher values in the ileum of the CARN lambs. Moreover, an increase in Ruminoclostridium, a cellulosomeproducing bacterium being able to metabolize branched plant polysaccharides, such as xyloglucan, was also observed in the CARN group (Ravachol et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Often, the modulatory impact of grains and carbohydrates on the gut microbiota is explained by fiber [49,50]. Fiber may influence the production of SCFA [51,52], which in turn has been associated with beneficial effects on a variety of metabolic and cardiovascular parameters, such as insulin and blood pressure [53,54]. However, in our cohort, the intake of fiber did not explain a significant part of the variance in Shannon index.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, inulin is described as propionogenic, whereas resistant starches are more butyrogenic. Of note, several colonic bacteria use alternative pathways to also produce butyrate from amino acids such as lysine or propionate from plant compounds such as phytate 70 71. It is worth noting that the sources of SCFAs are derived from the diet and they can originate from the host itself via the fermentation of the intestinal mucus that covers the intestinal epithelial cells 72…”
Section: Gut Microbes and Metabolic Disorders: Molecular Actorsmentioning
confidence: 99%